Cultivation of Navicula sp. on rice straw hydrolysate for the production of biogenic silica. (September 2022) - Dhali, Sumit; Jain, Rahul; Malik, Anushree; Sharma, Satyawati; Raliya, Ramesh
Graphical abstract: Highlights: First report on diatom ( Navicula sp.) cultivation in rice straw hydrolysate (RSH). Eco-friendly process to derive silica, nutrients, phenols apt for diatom growth. Biomass yield in 30% RSH increased by 1.85 folds compared to conventional media. Hydrolysate spent solid had 18.9% higher methane potential than untreated rice straw. Conversion of agricultural waste to valuable nano-porous biogenic silica material. Abstract: Rice straw hydrolysate (RSH) prepared at room temperature was found to be rich in silica (140 ± 4.1 mg L -1 ) and other nutrients (nitrate-N: 160 ± 4.3 mg L −1, total dissolve phosphate: 164 ± 6.7 mg L −1, ammoniacal-N: 439.8 ± 17 mg L −1 ). The aim of this work was to study four RSH dilutions (10, 30, 50, 70% v/v) to cultivate Navicula sp. with modified ASN-III as a control. The best result was achieved in 30% RSH in terms of doubling time (d = 1.49 days) and growth rate (µmax  = 0.46 day −1 ). Compared to control, specific growth rate and biomass productivity were increased by 2.93 folds and 1.85 folds, respectively. Cultivation in 5 L reactor with optimized 30% RSH yielded frustule (54.2 ± 1.9%), carbohydrate (12.4 ± 1.2%), lipid (18.9 ± 1.4%), and protein (8.2 ± 0.6%). The residual solid fraction showed 18.99% increased theoretical methane yield than raw rice straw. Overall, the present process offers a sustainable solution to manage rice straw residue and recover nanoporous silica.